Does GPER Really Function as a G Protein-Coupled Estrogen Receptor in vivo? - Luo, Jing; Liu, Dongmin (Frontiers in Endocrinology, 2020)
Estrogen can elicit pleiotropic cellular responses via a diversity of estrogen receptors (ERs)—mediated genomic and rapid non-genomic mechanisms. Unlike the genomic responses, where the classical nuclear ERα and ERβ act as transcriptional factors following estrogen binding to regulate gene transcription in estrogen target tissues, the non-genomic cellular responses to estrogen are believed to start at the plasma membrane, leading to rapid activation of second messengers-triggered cytoplasmic signal transduction cascades. The recently acknowledged ER, GPR30 or GPER, was discovered in human breast cancer cells two decades ago and subsequently in many other cells. Since its discovery, it has been claimed that estrogen, ER antagonist fulvestrant, as well as some estrogenic compounds can directly bind to GPER, and therefore initiate the non-genomic cellular responses. Various recently developed genetic tools as well as chemical ligands greatly facilitated research aimed at determining the physiological roles of GPER in different tissues. However, there is still lack of evidence that GPER plays a significant role in mediating endogenous estrogen action in vivo. This review summarizes current knowledge about GPER, including its tissue expression and cellular localization, with emphasis on the research findings elucidating its role in health and disease. Understanding the role of GPER in estrogen signaling will provide opportunities for the development of new therapeutic strategies to strengthen the benefits of estrogen while limiting the potential side effects.